Lignin-based sensor for heavy metal analysis in water - Tan, Perry Soon Ming (2017)
In this work, a conductive polymer polypyrrole (PPy) solely and PPy containing a complex organic polymer kraft lignin in its structure, were exploited as an ion to electron transducer in a solid contact lead(II) ion selective electrode (ISE) design/construction. PPy and PPy/lignin layers of different thickness (200, 500, and 1000, respectively) and lignin concentration (0.5, 1, and 2 mg/ml, respectively) were electro-polymerized on glassy carbon electrodes and with/without lead(II) ion selective membrane, casted on the surface to allow only Pb2+ ions migrate through the membrane, studied by different electrochemical methods. First of all, fundamental electrochemical properties, e.g., layer electric capacitivity, lignin redox activity, potential stability in terms of applied current (polarization), gas influence (acidifying and oxidative effect) of PPy and PPy/lignin layers solely (without the lead(II) ion selective membrane casted) were investigated and compared. Secondly, PPy and PPy/lignin layers, with and without the lead(II) ion selective membrane casted on top, were exploited in potentiometric measurements for lead(II) ion concentration determination in the concentration range from 10-7 to 10-1 M of Pb(NO3)2 in both buffered (pH 4) and un-buffered (pH varying between 7 to 4) solutions in order to optimize lead(II) ion concentration determination and improve the detection limit. It was found that the deposition of the lead(II) ion selective membrane lowered the detection limit when using both PPy and PPy/lignin-based electrodes since the membrane protected the polymer layers from the negative solution effect as well as enabled selective lead(II) ion penetration through the membrane. No effect of the presence of lignin within PPy structure was observed in terms of lead(II) ion concentration determination.